No-ozone cold plasma induces apoptosis in human neuroblastoma cell line via increased intracellular reactive oxygen species (ROS) - Jung-Han Lee; M Shriya Jaiswal; Yoon-Seo Jang; Jeong-Hae Choi; Gyoo-Cheon Kim; Jin-Woo Hong; Dae-Seok Hwang (BMC, 2024)
Abstract Background This study aimed to evaluate the effect of argon-based No-ozone Cold Plasma (NCP) on neuroblastoma cancer cell apoptosis. Methods Experiments were performed with SK-N-SH and HS 68. Cell cultures were treated with NCP for 1, 3, and 5 min. NCP was applied using three different strategies: direct NCP application to cell cultures, to only media, and to only cells. Evaluation of cell viability and the level of the reactive oxygen species (ROS) was performed. N-acetyl-L-cysteine (NAC) was also used to antagonize intracellular ROS. Cleaved caspase 3, PARP, aquaporin (AQP) 3 and 8 were detected. Results NCP induced a gradual decrease in the SK-N-SH cell viability. In contrast, the viability of HS 68 cells did not change. SK-N-SH cells viability was reduced the most when the only media-NCP application strategy was employed. Intracellular ROS levels were significantly increased with time. Cleaved caspase 3 and PARP were increased at 6 h after NCP application. SK-N-SH cells remained viable with NAC after NCP application. AQP 3 and 8 were over-expressed in SK-N-SH cells. Conclusion These findings demonstrate the anti-cancer effect of NCP on neuroblastoma cells. NCP enhanced the selective apoptosis of neuroblastoma cells due to the increased intracellular ROS.